Effects of gut microbiota on immune responses and immunotherapy in colorectal cancer - Hou, Xinxin; Zheng, Zongmei; Wei, Jiao; Zhao, Ling (Frontiers in Immunology, 2022)
Accumulating evidence suggests that gut microbial dysbiosis is implicated in colorectal cancer (CRC) initiation and progression through interaction with host immune system. Given the intimate relationship between the gut microbiota and the antitumor immune responses, the microbiota has proven to be effective targets in modulating immunotherapy responses of preclinical CRC models. However, the proposed putative mechanisms of how these bacteria affect immune responses and immunotherapy efficacy remains obscure. In this review, we summarize recent findings of clinical gut microbial dysbiosis in CRC patients, the reciprocal interactions between gut microbiota and the innate and/or the adaptive immune system, as well as the effect of gut microbiota on immunotherapy response in CRC. Increased understanding of the gut microbiota-immune system interactions will benefit the rational application of microbiota to the clinical promising biomarker or therapeutic strategy as a cancer immunotherapy adjuvant.